GEO- AND PHYTO-MONITORING OF ENVIRONMENTAL IMPACT OF SMELTING INDUSTRY IN IKIRUN, NIGERIA - Bello, Mojeed Olalekan; Abdus-Salam, N.; Odebunmi, N. A.; Jimoh, A. A. (FUDMA JOURNAL OF SCIENCES, 2021)
This research monitored the level of some heavy metals in soil and a plant species around iron smelting industry. The soil in different depths D1 (0 -10 cm), D2 (10 â€“ 20 cm) and D3 (20 -30 cm) and plant (Tithonia diversifolia) known as Mexican sunflower were sampled in four soil sampling points (SSP) and plant sampling points (PSP)  which are 50, 100, 150 and 200 m away from the industry. The concentrations of Cr, Cu, Fe, Pb and Zn in the soil and plant digest were determined using Atomic Absorption Spectroscopy (AAS). Some physicochemical properties like pH, electrical conductivity and organic matter were also measured. The result of the analysis of the heavy metals in the soil was in the sequence Fe > Zn > Cu >Pb> Cr at SSP1 SSP2 and SSP4 while Fe > Zn > Cu > Cr > Pb at SSP3. In the plant, the result showed the presence of these heavy metals except Pb which was not present in any sampling points. The concentration of iron (Fe) in the plant decreased away from PSP1 to PSP4 around the industry. The physicochemical properties like pH which influenced the availability of metals in soil were found to increase away from SSP1 to SSP4 and consequently its effect on the concentration of these heavy metals in plants, particularly for Fe and Zn. Although, heavy metals monitored were within the permissible limit of WHO except Fe in soil, the trend of their presence in